(untitled) (Journal of Economic Research & Business Administration, 2015)
In this article are considered the problems of Kazakhstan external debts, which are connected with the presence of external debt considerable volume, its low efficiency of the variety of foreign loans usage. In this case the detailed comparative analysis of external debts index-numbers of the Republic of Kazakhstan and certain countries of CIS is realized on the basis of statistical material of the World Bank for the period from 2008 to 2011. In the development of the Republic Kazakhstan external debt are traced the tendencies, which may provoke the development of the debt crisis in the future. In such conditions the absence of the exact improvement system of the debt situation may lead to the further extension of the current negative trends, making the country socio-economic development conditional from the problem decision of the external debt during the nearest decades. To determine the prospects of Kazakhstan borrowing there are calculated the optimally acceptable level of external debt in the med-term. The need to reduce the external debt rate of growth of the Republic of Kazakhstan stipulates to adopt a number of measures for optimization of the process of the foreign loans attraction and usage. In this regard, the author offers some recommendations to improve the management of Kazakhstan external debt of at the present stage.